(untitled) (European Journal of Pure and Applied Mathematics, 2025)
The theory of metric spaces forms the basis of metric fixed point theory, which has varied applications in the domain of various areas such as engineering, economics, medicine and even in space science such as launch of satellites etc. Nevertheless, fractal calculus too has varied applications. Metric spaces have been generalized and the fixed point results established under many contractive conditions in those newly defined spaces in the past few decades. In this work, we introduce neutrosophic bipolar metric spaces and establish fixed point theorems in these spaces. Our main results establish and generalize some proven results in the existing literature. The derived results have been strengthen with non trivial illustrations. Three applications are presented to supplement the derived results.